2022
DOI: 10.1063/5.0103138
|View full text |Cite
|
Sign up to set email alerts
|

Approximate solution to a generalized Van der Pol equation arising in plasma oscillations

Abstract: Motivated by some published theoretical investigations and based on the two-fluid model, nonlinear plasma oscillations are analyzed and discussed in the framework of the generalized Van der Pol equation. This equation is analyzed and solved using two different analytical approaches. In this first approach, the ansatz method is carried out for deriving an approximation in the form of a trigonometric function. In the second approach, the Krylov–Bogoliubov–Mitropolsky (KBM) technique is applied for obtaining a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The analytical solution (13) and the approximate solution ( 16) to the i.v.p. ( 1) and the exact solution (20) to the i.v.p. (19) (linearized form to the i.v.p.…”
Section: Conserved Rotational Pendulum Oscillatormentioning
confidence: 99%
See 2 more Smart Citations
“…The analytical solution (13) and the approximate solution ( 16) to the i.v.p. ( 1) and the exact solution (20) to the i.v.p. (19) (linearized form to the i.v.p.…”
Section: Conserved Rotational Pendulum Oscillatormentioning
confidence: 99%
“…The model of nonlinear oscillators that describes the motion of different types of pendulum oscillators with different rotations and directions is one of the most successful models for describing and modeling many physical and engineering applications such as the wind vibration [11][12][13][14][15][16][17][18][19][20]. To find an exact solution to the dynamical system of the pendulum oscillation is not an easy task, and sometimes it can be impossible due to its nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 20) considers the influence of current, the result is still a cosine function. Therefore, the KBM method [43] is used to further improve the solution accuracy. In the KBM method, the displacement x, the amplitude a, and the phase  in Eq.…”
Section: Undamped Vibration Analysis Of the Electromagnetic Systemmentioning
confidence: 99%
“…They found that both the analytical and numerical solutions were completely identical, which confirmed the high efficiency of the KBM approximations. Moreover, the KBMM was implemented to find a highly accurate analytic approximation to the generalized VdP oscillatory equation [16]. Both forced and unforced damped/undamped parametric pendulum oscillatory equations were analyzed to obtain approximate solutions using certain effectiveness, and more accurate, analytical and numerical techniques, including He's frequency-amplitude formulation, He's HPM, the KBMM, and many others [17].…”
mentioning
confidence: 99%